2010
DOI: 10.1080/01609510903366228
|View full text |Cite
|
Sign up to set email alerts
|

“We may not like it but we guess we have to do it:” Bringing Agency-Based Staff on Board with Evidence-Based Group Work

Abstract: In this article the authors describe our experience of developing a manualized model of group treatment for early adolescents with learning disabilities. We review the process of developing and piloting the manual as part of a school-based intervention research project, and the process and complexities in using this model in a community agency with a long history of conducting groups. The authors provide the leaders' feedback on their experience of co-leading a manualized group approach. They conclude with pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Thus, a lack of sufficient time, aligned with other factors like a dearth of resources and negative or skeptical attitudes, are possible hindering factors, that are also described in previous research (Gray, Joy, Plath, & Webb, 2014;Heiwe et al, 2013;Pope, Rollins, Chaumba, & Risler, 2011;Scurlock-Evans & Upton, 2015). Another possible consequence of limited time is practitioners' choice to work from experience and tacit knowledge, instead of basing choices on evidence, since this requires less effort in comparison (Muskat, Mishna, Farnia, & Wiener, 2010). The evident struggle with time, for both reflective practice and working with specific models, needs to be analyzed in relation to previous and current trends in the field of social work, as mentioned in the introduction.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Thus, a lack of sufficient time, aligned with other factors like a dearth of resources and negative or skeptical attitudes, are possible hindering factors, that are also described in previous research (Gray, Joy, Plath, & Webb, 2014;Heiwe et al, 2013;Pope, Rollins, Chaumba, & Risler, 2011;Scurlock-Evans & Upton, 2015). Another possible consequence of limited time is practitioners' choice to work from experience and tacit knowledge, instead of basing choices on evidence, since this requires less effort in comparison (Muskat, Mishna, Farnia, & Wiener, 2010). The evident struggle with time, for both reflective practice and working with specific models, needs to be analyzed in relation to previous and current trends in the field of social work, as mentioned in the introduction.…”
Section: Discussionmentioning
confidence: 85%
“…Or put differently, what creates ineffective organizations is a constant trial of new solutions, thus never allowing any one of them to become routinized, (March, 1991, in SOU, 2018). If working with new approaches implies a struggle for the practitioner, falling back on previous approaches, like basing work solely on experience, is a risk (Muskat et al, 2010).By investigating the actual need for new knowledge and treatments in the work-group/organization, while both bearing clientele and surrounding factors in mind and planning ahead in terms of training, practice can be well thought-through, priorities determined, and resources saved.…”
Section: Discussionmentioning
confidence: 99%
“…Six articles reported findings from a study where the core research question related to the use of treatment manuals (Addis and Krasnow, ; Ashcraft et al., ; Morgenstern et al., ; Simmons et al., ; Staudt and Williams‐Hayes, , Wallace and von Ranson, ). A further six described the development, evaluation or implementation of a manual (Busch et al ., ; Gregory and Macpherson, ; Herschell et al., ; Muskat et al., ; Stith et al., ; Taylor et al., ). Two studies reported evidence of the use of manuals in the context of eating disorders (Simmons et al., ; Wallace and von Ranson, ), one on domestic violence (Stith et al ., ) one on addictions (Morgenstern, et al., ) and one on anxiety/panic disorder (Busch et al., ).…”
Section: Description Of Studiesmentioning
confidence: 99%
“…The articles reported a number of beliefs about adherence, or fidelity, to manuals, the possibilities for creativity in their use (both in content and in the length of therapy), the nature and presence of therapeutic alliance and the overall acceptability of manuals. Several studies found that clinicians believe that manuals lead to loss of skills and dissatisfied therapists, as they are considered to be dry and uninteresting (Addis and Krasnow, ; Morgenstern et al., ; Muskat et al., ; Stith et al., ; Wallace and von Ranson, ). Such claims must be interpreted in the light of the respondents' self‐reported awareness of manuals.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation